2013
DOI: 10.1016/j.ijlcj.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Does a therapeutic court context matter?: The likelihood of imprisonment for Indigenous and non-Indigenous offenders sentenced in problem-solving courts

Abstract: A key aspect of the focal concerns perspective of sentencing is that time and information restrictions within the courtroom create the conditions under which perceptual shorthands may impact sentencing determinations. These shorthands are based stereotypes related to offender characteristics including minority group statuses (i.e. ethnicity, race, Indigenous status) (Steffensmeier et al., 1998). To date, sentencing scholars drawing on the focal concerns perspective have only considered the impact of minority g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…There is a now growing body of multivariate statistical analyses in Australia on Indigeneity and sentencing outcomes in the mainstream courts (both higher and lower), problem-solving courts and Indigenous courts. Overall, there is strong evidence of parity (and leniency in one jurisdiction, South Australia) in the likelihood of a prison sentence in the higher criminal courts, as well as evidence that there is a lower likelihood of imprisonment for Indigenous defendants in the problem-solving and Indigenous courts (Bond & Jeffries, 2012a, 2012b, 2011; Jeffries & Bond, 2009, 2013; Snowball & Weatherburn, 2007). However, in the conventional lower courts, research suggests that Indigenous offenders may be more likely to receive a prison sentence compared to similarly situated non-Indigenous offenders (Bond & Jeffries, 2012b; Jeffries & Bond, 2011, 2012).…”
Section: Prior Research On Sentencing Domestic Violence and Indigeneitymentioning
confidence: 99%
“…There is a now growing body of multivariate statistical analyses in Australia on Indigeneity and sentencing outcomes in the mainstream courts (both higher and lower), problem-solving courts and Indigenous courts. Overall, there is strong evidence of parity (and leniency in one jurisdiction, South Australia) in the likelihood of a prison sentence in the higher criminal courts, as well as evidence that there is a lower likelihood of imprisonment for Indigenous defendants in the problem-solving and Indigenous courts (Bond & Jeffries, 2012a, 2012b, 2011; Jeffries & Bond, 2009, 2013; Snowball & Weatherburn, 2007). However, in the conventional lower courts, research suggests that Indigenous offenders may be more likely to receive a prison sentence compared to similarly situated non-Indigenous offenders (Bond & Jeffries, 2012b; Jeffries & Bond, 2011, 2012).…”
Section: Prior Research On Sentencing Domestic Violence and Indigeneitymentioning
confidence: 99%
“…In problem-solving courts, however, caseloads are smaller by design, judges meet more frequently with defendants to determine treatment progress, and they have access to much more detailed information about defendants. Often there are weekly meetings between case managers, treatment providers, attorneys, correctional agents, and judges, which provide detailed information about offender progress and compliance with court conditions (Jeffries & Bond, 2013;Ray & Dollar, 2013). Finally, problem-solving courts are distinguished by their reliance on therapeutic jurisprudence and emphasis on rehabilitation of offenders (Worrall, 2008).…”
Section: Case Processing As Symbolic Interaction With Discursive Procmentioning
confidence: 99%
“…Less commonly examined is the intersection of race and gender identity in constructing defendants' actions. Jeffries and Bond (2013) observed sentencing hearings for women defendants in an Australian court. They found that judges weigh focal concerns of blameworthiness, recidivism risk, and practical constraints differently for Indigenous women compared to non-Indigenous women.…”
Section: Racial Discourses In Court Hearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating variations, trends, disparities and disadvantage in sentencing outcomes entails modelling the effects of a series of independent variables on sentences (for example, Bushway and Piehl 2001;Bushway et al 2012;Fischman and Schanzenbach 2012;Light 2014;Wooldredge et al 2011). Typical independent variables relate to the nature of the offence and offender characteristics, usually race/ethnicity, gender, age and socio-economic status (Bond and Jeffries 2012;Doerner and Demuth 2010;Hood 1992;Jeffries and Bond 2013;Shute et al 2013). Measures of sentence outcomes include sentenced to prison (yes/no) and length of sentence (Steffensmeier and Demuth 2001;Ulmer and Johnson 2004).…”
Section: The Judge Within Social Science Research: Sentencing Patternsmentioning
confidence: 99%